Autarchy, Market Disintegration, and Health: The Mortality and Nutritional Crisis in Nazi Germany, 1933-1937 - Jörg Baten; Andrea Wagner (Center for Economic Studies and ifo Institute (CESifo), 2002)
We compare trends in mortality, nutritional status and food supply to other living standard indicators for the early years of the Nazi period. We find that Germany experienced a substantial increase in mortality rates in most age groups in the mid-1930s, even relative to those of 1932, the worst year of the Great Depression. Expenditures on rearmament grew at the expense of public health measures. Food imports were curtailed, and prices of many agricultural products were controlled. There is ample evidence that this set of economic policies had an adverse effect on the health of the population.
Keywords: 330